Hypericum perfolatum Oil-Loaded Niosomal Gel for Vaginal Delivery - Özyılmaz, Emine Dilek (Society of Pharmaceutical Sciences of Ankara (FABAD), 2025)
The objective of this study is to formulate and assess a niosomal gel formulation with Hypericum perforatum oil for potential vaginal administration. Different Span®60:Tween®80 ratios (1:1, 1:2, and 2:1) were used to prepare the niosomes using the thin-film hydration method, and the physicochemical properties of the prepared niosomes were assessed by particle size, polydispersity index (PDI), and zeta potential. The F2 formulation was selected based on optimal particle size and stability conditions. Morphological analysis with SEM confirmed spherical and homogeneously dispersed vesicles. The selected niosomal formulation was incorporated into a 2% HPMC gel base to prepare a vaginal gel product. The developed gel had an adequate viscosity (17,000 ± 0.520 cP), a physiologically relevant pH value (5.5 ± 0.2), and an effective entrapment of Hypericum oil (71.6 ± 0.4%). In vitro drug release studies across a cellulose membrane showed sustained release of the niosomal gel compared to the non-niosomal product. Stability studies conducted over 3 months under accelerated stability conditions revealed negligible changes in physicochemical properties. Overall, the niosomal gel system efficiently promoted the retention and controlled release of Hypericum perforatum oil, justifying its potential as a promising carrier for vaginal drug delivery purposes. © 2025, Society of Pharmaceutical Sciences of Ankara (FABAD). All rights reserved.
Vajinal İçin Hypericum perfolatum Yağ Yüklü Niosomal Jel
Keywords: HPMC vaginal gel; Hypericum perforatum oil; niosomes; stability